2023
DOI: 10.1186/s12967-023-04076-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical features, genomic landscapes and survival outcomes in HER2-low breast cancer

Abstract: Background Novel human epidermal growth factor receptor 2 (HER2)-directed antibody–drug conjugates prompt the identification of the HER2-low subtype. However, the biological significance of HER2-low expression in breast cancer is unclear. Methods Clinical and genomic data of 579 metastatic breast cancer patients were reviewed from our next-generation sequencing (NGS) database and genomic analysis of early breast cancer patients from TCGA was also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Jin et al [ 15 ] conducted next-generation sequencing on their metastatic breast cancer (mBC) cohort (n=445) and the TCGA dataset. They found no significant differences in common gene mutations and copy number variations between HER2- low and HER2-zero tumors after correcting for HR status.…”
Section: Characteristics Of Her2-low Tumorsmentioning
confidence: 99%
“…Jin et al [ 15 ] conducted next-generation sequencing on their metastatic breast cancer (mBC) cohort (n=445) and the TCGA dataset. They found no significant differences in common gene mutations and copy number variations between HER2- low and HER2-zero tumors after correcting for HR status.…”
Section: Characteristics Of Her2-low Tumorsmentioning
confidence: 99%
“…Recent studies suggest that HER2-low breast cancer may have different clinicopathological characteristics and outcomes compared to HER2-positive or HER2-negative breast cancers [ [5] , [6] , [7] ]. Two recent studies conducted by Guven et al [ 8 ] and Jin et al [ 9 ] have both demonstrated a correlation between HER2-low disease and an elevated risk of brain metastasis compared with HER2-zero breast cancer, particularly within the HR-positive subgroup.…”
Section: Introductionmentioning
confidence: 99%